2010
DOI: 10.1111/j.1742-1241.2009.02267.x
|View full text |Cite
|
Sign up to set email alerts
|

The Glasgow Blatchford scoring system enables accurate risk stratification of patients with upper gastrointestinal haemorrhage

Abstract: The GBS accurately identifies low risk patients who could be managed safely as outpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 20 publications
8
41
0
1
Order By: Relevance
“…Endoscopic results in the low-and high-risk groups of patients An ideal scoring system should have both a good sensitivity and high specificity. However, in the studies conducted, the sensitivity and specificity of the GBS system vary among high-risk patients with UGI system bleeding (10,12,13). In our study, the sensitivity and specificity were 100% and 1.41% for a cut-off value of GBS >0, 100% and 16.9% for a cut-off value of GBS >3, 96.63% and 36.62% for a cut-off value of GBS >5, and 86.52% and 69.01% for a cut-off value of GBS >8.…”
Section: Referred 16mentioning
confidence: 98%
See 1 more Smart Citation
“…Endoscopic results in the low-and high-risk groups of patients An ideal scoring system should have both a good sensitivity and high specificity. However, in the studies conducted, the sensitivity and specificity of the GBS system vary among high-risk patients with UGI system bleeding (10,12,13). In our study, the sensitivity and specificity were 100% and 1.41% for a cut-off value of GBS >0, 100% and 16.9% for a cut-off value of GBS >3, 96.63% and 36.62% for a cut-off value of GBS >5, and 86.52% and 69.01% for a cut-off value of GBS >8.…”
Section: Referred 16mentioning
confidence: 98%
“…Although in the literature, there has been no consensus on the best scoring system in various studies performed using the Rockall scoring system and/or the GBS system (3,10,(12)(13)(14)(15)(16)(17), the GBS system seems to be more useful, especially in patients with non-variceal UGI system bleeding. In our study, which included all the patients with variceal and non-variceal UGI system bleeding, we used the GBS system, and found it useful in the differentiation of high-risk patients.…”
Section: Low-risk (N) High-risk (N)mentioning
confidence: 99%
“…In this cohort of patients the 28 d mortality rate was 0 [43] . The GBS has been shown to be as good as the Rockall score in predicting the need for any intervention, namely the need for therapeutic endoscopy [41,42,[44][45][46][47] . The GBS has also been shown to be superior to the clinical Rockall score in identifying patients with suspected UGIB who have a low likelihood of an adverse clinical outcome (blood transfusion, endoscopic therapy, interventional radiology, surgery or 30 d mortality) and can be considered for early discharge [48] .…”
Section: The Importance Of Outcomesmentioning
confidence: 99%
“…The reported conclusion is that the modified GBS performed as well as the full GBS while outperforming both clinical and endoscopic Rockall Scores for prediction of clinical outcomes [51] . Some studies have suggested that the rate of identified lowrisk patients could be increased by using a higher GBS cut-off value [45,[52][53][54][55][56][57] or by incorporating age as a variable [52,58] .…”
Section: The Importance Of Outcomesmentioning
confidence: 99%
See 1 more Smart Citation